Hyperbaric Oxygen Therapy for Traumatic Brain Injury: A Review Of History, Development, Current Techniques, and Future Directions - Wiwoho, Yudi Yuwono; Sadikin, Abdul Halim; Jusuf, Ahmad Aulia; Mulyawan, Wawan; Mudjihartini, Ninik; Ibrahim, Nurhadi; Jusman, Sri Widia A.; Sadikin, Mohamad (Writing Center IMERI FMUI, 2025)
Hyperbaric oxygen therapy (HBOT) has gained increasing attention as a potential adjunctive treatment for traumatic brain injury (TBI) patients. This narrative review discusses the historical background, current preclinical and clinical studies, and explores its underlying mechanisms from biomolecular, histological, and clinical perspectives. HBOT promotes neural recovery by improving oxygenation, preserving mitochondrial integrity, enhancing neurotrophic support and synaptic connectivity, mitigating secondary injury pathways (including oxidative stress, inflammation, and apoptosis), and promoting angiogenesis and vascular stability. These mechanisms have demonstrated improvements of motor, cognitive, and memory functions both in preclinical and clinical studies, although outcomes and treatment protocols vary. However, challenges remain regarding optimal protocols, patient selection, and adverse effects. Further high-quality clinical trials are required to define the optimal HBOT regimen are required.